Analisis Evaluasi Pendidikan Karakter Peserta Didik Dalam Manajemen Kurikulum 2013 Di Sekolah Pedesaan Dan Perkotaan - Deitje Adolfien Katuuk; Meytha Meyske Wongkar; Samuel Harry Mossey; Davison Pagawak (Departement of Mathematics Education, 2024)
This research aims to analyze the evaluation of students' character education in the 2013 curriculum management in rural and urban schools. This research uses qualitative methods with library study techniques based on data all sourced from national journal databases. At the same time, appropriate search terms are a prerequisite for accurate data acquisition. To make search results as comprehensive and accurate as possible, the Authorb of Science core collection was selected for this study. This research uses the subject